1980
DOI: 10.1073/pnas.77.10.5606
|View full text |Cite
|
Sign up to set email alerts
|

Geminate recombination of O2 and hemoglobin.

Abstract: The photolysis of HbO2 and HbCO has been studied by measuring transient absorption spectra in the Soret region after excitation with picosecond pulses at 530 nm. Dissociation occurred promptly in both cases, followed (for HbO2) by geminate recombination of ca. 40% of the photodissociated O2 with a lifetime of 200 ± 70 psec (25°C). No to 300 psec. The initial MbCO photoproduct signal at 440 nm was reported to undergo a 15% decay (lifetime r = 125 + 50 psec), but for MbO2 no evidence of decay up to 450 psec wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
6

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 30 publications
4
89
0
6
Order By: Relevance
“…We have therefore carried out picosecond laser experiments on Mb aimed at characterizing the fluorescent behavior of each of the tryptophans. Previous picosecond laser experiments aimed at detecting rapid conformational changes and relaxation processes in heme proteins have involved studying changes in the heme electronic structure as a result of photodeligation of CO (1)(2)(3)(4)(5)(6), 02 (1,(4)(5)(6), and NO (6,7). A goal of the present research is to pave the way for the study of the transmission of structural changes throughout the protein, and as a first step we have attempted in the present work to chart the picosecond anatomy of the tryptophans of Mb.…”
mentioning
confidence: 99%
“…We have therefore carried out picosecond laser experiments on Mb aimed at characterizing the fluorescent behavior of each of the tryptophans. Previous picosecond laser experiments aimed at detecting rapid conformational changes and relaxation processes in heme proteins have involved studying changes in the heme electronic structure as a result of photodeligation of CO (1)(2)(3)(4)(5)(6), 02 (1,(4)(5)(6), and NO (6,7). A goal of the present research is to pave the way for the study of the transmission of structural changes throughout the protein, and as a first step we have attempted in the present work to chart the picosecond anatomy of the tryptophans of Mb.…”
mentioning
confidence: 99%
“…The dissociation of CO was immediate and there was no geminate recombination. The dissociation of oxygen from HbO 2 was also immediate but we discovered a 200-ps geminate recombination of the oxygen molecules (61). The nitric oxide ligand of HbNO dissociated immediately followed by a very rapid nonexponential geminate recombination of the NO (62).…”
Section: Biophysical Chemistrymentioning
confidence: 91%
“…One such process that is readily studied is geminate recombination [7][8][9] which is known to occur both on the sub-ns [16] and many 10's of ns [7][8][9] time scale for photodissociated 02. Recent studies (in preparation) on oxy-and nitroxy-Hb's have revealed that for human Hb and turtle Hb the yield of geminate recombination occurring over a 10 ns pulse correlates with the frequency of both v4 and the Fe-His stretching mode which are themselves correlated.…”
Section: Methodsmentioning
confidence: 99%